2023
DOI: 10.3389/fphar.2022.1104735
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolism and tolerability of racemic primaquine and its enantiomers in human volunteers during 7-day administration

Abstract: Primaquine (PQ) is an 8-aminoquinoline antimalarial, active against dormant Plasmodium vivax hypnozoites and P. falciparum mature gametocytes. PQ is currently used for P. vivax radical cure and prevention of malaria transmission. PQ is a racemic drug and since the metabolism and pharmacology of PQ’s enantiomers have been shown to be divergent, the objectives of this study were to evaluate the comparative tolerability and metabolism of PQ with respect to its two enantiomers in human volunteers in a 7 days’ trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The difference in plasma concentrations between the two tafenoquine enantiomers in human trials was found to be less than 10% . Enantiomers of 8-aminoquinolines have been shown to differ in the terms of their antimalarial activity. , …”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The difference in plasma concentrations between the two tafenoquine enantiomers in human trials was found to be less than 10% . Enantiomers of 8-aminoquinolines have been shown to differ in the terms of their antimalarial activity. , …”
Section: Resultsmentioning
confidence: 96%
“… 46 Primaquine and tafenoquine are the only available treatments which are active against both the liver hypnozoites and the sexual blood stages of malaria. 55 The difference in plasma concentrations between the two tafenoquine enantiomers in human trials was found to be less than 10%. 56 Enantiomers of 8-aminoquinolines have been shown to differ in the terms of their antimalarial activity.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations